Collagen scaffolds functionalized with triple-helical peptides support 3D HUVEC culture. Issue 5 (18th August 2020) - Malcor, Jean-Daniel; Hunter, Emma J; Davidenko, Natalia; Bax, Daniel V; Cameron, Ruth; Best, Serena; Sinha, Sanjay; Farndale, Richard W
Abstract: Porous biomaterials which provide a structural and biological support for cells have immense potential in tissue engineering and cell-based therapies for tissue repair. Collagen biomaterials that can host endothelial cells represent promising tools for the vascularization of engineered tissues. Three-dimensional collagen scaffolds possessing controlled architecture and mechanical stiffness are obtained through freeze–drying of collagen suspensions, followed by chemical cross-linking which maintains their stability. However, cross-linking scaffolds renders their biological activity suboptimal for many cell types, including human umbilical vein endothelial cells (HUVECs), by inhibiting cell–collagen interactions. Here, we have improved crucial HUVEC interactions with such cross-linked collagen biomaterials by covalently coupling combinations of triple-helical peptides (THPs). These are ligands for collagen-binding cell-surface receptors (integrins or discoidin domain receptors) or secreted proteins (SPARC and von Willebrand factor). THPs enhanced HUVEC adhesion, spreading and proliferation on 2D collagen films. THPs grafted to 3D-cross-linked collagen scaffolds promoted cell survival over seven days. This study demonstrates that THP-functionalized collagen scaffolds are promising candidates for hosting endothelial cells with potential for the production of vascularized engineered tissues in regenerative medicine applications.